Benefits of pulmonary rehabilitation in COVID-19: a prospective observational cohort study. Issue 2 (31st May 2021) - Gloeckl, Rainer; Leitl, Daniela; Jarosch, Inga; Schneeberger, Tessa; Nell, Christoph; Stenzel, Nikola; Vogelmeier, Claus F.; Kenn, Klaus; Koczulla, Andreas R.
Background: Coronavirus disease 2019 (COVID-19) can result in a large variety of chronic health issues such as impaired lung function, reduced exercise performance and diminished quality of life. Our study aimed to investigate the efficacy, feasibility and safety of pulmonary rehabilitation in COVID-19 patients and to compare outcomes between patients with a mild/moderate and a severe/critical course of the disease. Methods: Patients in the post-acute phase of a mild to critical course of COVID-19 admitted to a comprehensive 3-week inpatient pulmonary rehabilitation programme were included in this prospective, observational cohort study. Several measures of exercise performance (6-min walk distance (6MWD)), lung function (forced vital capacity (FVC)) and quality of life (36-question short-form health survey (SF-36)) were assessed before and after pulmonary rehabilitation. Results: 50 patients were included in the study (24 with mild/moderate and 26 with severe/critical COVID-19). On admission, patients had a reduced 6MWD (mild: median 509 m, interquartile range (IQR) 426–539 m; severe: 344 m, 244–392 m), an impaired FVC (mild: 80%, 59–91%; severe: 75%, 60–91%) and a low SF-36 mental health score (mild: 49 points, 37–54 points; severe: 39 points, 30–53 points). Patients attended a median (IQR) 100% (94–100%) of all provided pulmonary rehabilitation sessions. At discharge, patients in both subgroups improved in 6MWD (mild/moderate: +48 m, 35–113 m; severe/critical: +124 m, 75–145 m; both p<0.001), FVC (mild/moderate: +7.7%, 1.0–17.8%, p=0.002; severe/critical: +11.3%, 1.0–16.9%, p<0.001) and SF-36 mental component (mild/moderate: +5.6 points, 1.4–9.2 points, p=0.071; severe/critical: +14.4 points, −0.6–24.5, p<0.001). No adverse event was observed. Conclusion: Our study shows that pulmonary rehabilitation is a feasible, safe and effective therapeutic option in COVID-19 patients independent of disease severity. Pulmonary rehabilitation is effective, feasible and safe to improve exercise performance, lung function and quality of life in patients with persistent impairments due to a mild to critical course of #COVID19 https://bit.ly/3kQFIbs